Approximative characteristics of the Nikol’skii – Besov classes of functions S_1, θ^r B(R^d) - Radchenko, O. Ya.; Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.51 We establish the exact-order estimates for the approximation of the classes S^r _1,θB (R^d) by entire functions of exponential type with supports of their Fourier transforms lying in a step hyperbolic cross. The error of approximation is estimated in the metric of the Lebesgue space L_q(R^d), 1 < q ≤ ∞.